Computational fluid dynamics simulation of exhaust ventilation and jet fan systems during a fire event in velodrome / Sayed Mojtaba Tabibian - Sayed Mojtaba, Tabibian (2017)
Ensuring human safety in the case of fire in tunnels, buildings, car parks or any other premises is one of the objectives of fire engineering design. Many researchers have focused on fire safety elements like heat, velocity and smoke dynamics because many fire victims are killed by toxic gases and smoke items such as carbon monoxide induced by fire. Carbon monoxide poses the most deadly risk to people and will not easily be discharged. In this study, the effectiveness of ventilation system in fire safety is investigated by using computational fluid dynamics (CFD) simulation results on smoke spill. The case study was conducted at Velodrome (Indoor) to determine the smoke propagation and air flow pattern during fire. For this purpose, the full scale model has been developed in the CFD with the total of four million elements for mesh generation. The velocity inlet was adopted for fresh air inlets form doors as well as mass flow of fire. Outflow was selected for exhaust ducting system. About 4 MW fire at two different positions were simulated at the Velodrome and the time based simulation was done for total of 0-90 minutes considering evacuation time. The effect of the smoke spill by simulating with exhausted system for both switched “ON” and “OFF” of the simulator. Also the results were investigated and analyzed in 3-dimensional plane. The results for velocity, smoke, and temperature distributions are presented at 2m, 4m, 10m, and 13m height from floor level for both of fire position scenarios. This study focuses on the problem of smoke evacuation and the possibility of operating the fans and exhausted system, during different fire at Velodrome. The primary goal of smoke management is to facilitate safe exit in the case of fire and it is also crucial in saving a property since it is more costly to maintain it than to build it. Thus, the control and removal of smoke and gases from burning building is a vital component in any fire protection scheme. The findings demonstrate that by activating a fan and exhaust system, the risk of people’s life and damaged property can be reduced because the source of fire can be removed completely and thus, smoke poses no threat.